Different Styles, Different Times: How Response Times Can Inform Our Knowledge About the Response Process in Rating Scale Measurement. (July 2021) - Henninger, Mirka; Plieninger, Hansjörg
When respondents use different ways to answer rating scale items, they employ so-called response styles that can bias inferences drawn from measurement. To describe the influence of such response styles on the response process, we investigated relations between extreme, acquiescent, and mid response style and response times in three studies using multilevel modeling. On the response level, agreement and midpoint, but not extreme responses were slower. On the person level, response times increased for extreme, but not for acquiescence or mid response style traits. For all three response styles, we found negative cross-level interaction effects, indicating that a response matching the response style trait is faster. The results demonstrate that response styles facilitate the choice of specific category combinations in terms of response speed across a wide range of response style trait levels.